A high-volume, low-cost approach to participant screening and enrolment: Experiences from the T4DM diabetes prevention trial. (December 2019) - Bracken, Karen; Keech, Anthony; Hague, Wendy; Allan, Carolyn; Conway, Ann; Daniel, Mark; Gebski, Val; Grossmann, Mathis; Handelsman, David J; Inder, Warrick J; Jenkins, Alicia; McLachlan, Robert; et al.
Background/aims: Participant recruitment to diabetes prevention randomised controlled trials is challenging and expensive. The T4DM study, a multicentre, Australia-based, Phase IIIb randomised controlled trial of testosterone to prevent Type 2 diabetes in men aged 50–74 years, faced the challenge of screening a large number of prospective participants at a small number of sites, with few staff, and a limited budget for screening activities. This article evaluates a high-volume, low-cost, semi-automated approach to screen and enrol T4DM study participants. Methods: We developed a sequential multi-step screening process: (1) web-based pre-screening, (2) laboratory screening through a network of third-party pathology centres, and (3) final on-site screening, using online data collection, computer-driven eligibility checking, and automated, email-based communication with prospective participants. Phone- and mail-based data collection and communication options were available to participants at their request. The screening process was administered by the central coordinating centre through a central data management system. Results: Screening activities required staffing of approximately 1.6 full-time equivalents over 4 years. Of 19, 022 participants pre-screened, 13, 108 attended a third-party pathology collection centre for laboratory screening, 1217 received final, on-site screening, and 1007 were randomised. In total, 95% of the participants opted for online pre-screening over phone-based pre-screening. Screening costs, including both direct and staffing costs, totalled AUD1, 420, 909 (AUD75 per subject screened and AUD1411 per randomised participant). Conclusion: A multi-step, semi-automated screening process with web-based pre-screening facilitated low-cost, high-volume participant enrolment to this large, multicentre randomised controlled trial. Centralisation and automation of screening activities resulted in substantial savings compared to previous, similar studies. Our screening approach could be adapted to other randomised controlled trial settings to minimise the cost of screening large numbers of participants.